Pengaruh e–marketing dan e-comerce terhadap pendapatan usaha umkm di tengah pandemi covid 19 (studi kasus kecamatan duren sawit) the effect of e - marketing and e commerce on msme business revenue in the middle of the Covid-19 pandemic (case study of Duren Sawit District) - Rinny Yudowati; Dwi Handiatmoko (Journal of Information System, Applied, Management, Accounting and Research, 2021)
This study aims to determine the effect of e-marketing and e-commerce on MSME business income in the midst of the COVID-19 pandemic (case study of Duren Sawit sub-district). With the COVID-19 pandemic and the Government's appeal regarding social distancing launched on March 15, 2020, it is predicted to have a serious impact on the absorption of MSME products. So that it requires business actors to be technology literate in dealing with covid 19 by utilizing social media as a marketing tool and e-commerce as a transaction tool which is expected to have a positive influence on MSME business income in the midst of the covid 19 pandemic until post covid 19. By using the Slovins Theory, a sample of 133 respondents of MSME actors under the guidance of Duren Sawit Sub-district were obtained. Two approaches were taken, namely, descriptive approach by describing existing phenomena and quantitative where data collection used observation and interview techniques. The research location was conducted in the Duren Sawit District, East Jakarta. The independent variables are E Marketing and E Commerce, the dependent variable is MSME Business Income in the midst of the covid 19 pandemic. The data source in this study is the MSME actors fostered by the Duren Sawit sub-district which are registered under the PKT (Integrated Entrepreneurship Development) facilitator in the Duren sSawit sub-district in 2021. The results show that E-marketing and E-commerce have an effect on MSME income in the midst of the Covid 19 pandemic.